Cardiorespiratory demands of firearms training instruction and 15m shuttle tests in British law enforcement. - Joseph Warwick; Sophie Cooper; Flaminia Ronca (PLoS ONE)
Objectives Law enforcement agencies require minimum fitness standards to safeguard their officers and training staff. Firearms instructors (FI) are expected to maintain the same standards as their operational counterparts. This study aimed to quantify the daily physiological demands placed on FI. Methods 19 FI (45 ± 5 years) completed occupational tasks whilst wearing heart rate (HR) monitors for a minimum 10 days. Maximal oxygen consumption (VO2max) testing was conducted on FI during a treadmill test (TT) and a multistage shuttle test (ST). Linear regression models were used to model the relationship between VO2 and HR throughout the TT. This model was applied to HR data from occupational tasks to infer oxygen consumption. Repeated Measures ANOVAs were used to compare time spent in VO2max equivalent zones throughout. Results The VO2max achieved during ST (45.1 ± 5.6 ml/kg/min) was significantly higher than TT (39 ± 3 ml/kg/min) (p = 0.014). Time to exhaustion (TTE) was sooner on ST (06:26 min) compared to TT (13:16 min) (p < .001). FI spent ~85% of occupational time with an oxygen demand ≤20 ml/kg/min (p < .005). The most intense occupational tasks saw FI achieve VO2max ≥30 ml/kg/min, but <40 ml/kg/min. Conclusion Using ST to assess cardiorespiratory fitness resulted in a quicker TTE and a higher VO2max. Predominantly, FI occupational tasks are low intensity with sporadic exposures requiring a VO2max of >40 ml/kg/min. To safeguard FI from occupational-related cardiorespiratory or long-term health issues, it is intuitive to suggest fitness standards should exceed a VO2max of 40 ml/kg/min.